Stable mid-infrared polarization imaging based on quasi-2D tellurium at room temperature - Tong, Lei; Huang, Xinyu; Wang, Peng; Ye, Lei; Peng, Meng; An, Licong; Sun, Qiaodong; Zhang, Yong; Yang, Guoming; Li, Zheng; Zhong, Fang; Wang, Fang; et al. (Nature communications, 2020)
Next-generation polarized mid-infrared imaging systems generally requires miniaturization, integration, flexibility, good workability at room temperature and in severe environments, etc. Emerging two-dimensional materials provide another route to meet these demands, due to the ease of integrating on complex structures, their native in-plane anisotropy crystal structure for high polarization photosensitivity, and strong quantum confinement for excellent photodetecting performances at room temperature. However, polarized infrared imaging under scattering based on 2D materials has yet to be realized. Here we report the systematic investigation of polarized infrared imaging for a designed target obscured by scattering media using an anisotropic tellurium photodetector. Broadband sensitive photoresponse is realized at room temperature, with excellent stability without degradation under ambient atmospheric conditions. Significantly, a large anisotropic ratio of tellurium ensures polarized imaging in a scattering environment, with the degree of linear polarization over 0.8, opening up possibilities for developing next-generation polarized mid-infrared imaging technology. Photodetectors operating within scattering environment can be realized with anisotropic materials. Here, the authors report polarization sensitive photodetectors based on thin tellurium nanosheets with high photoresponsivity of 3.54 × 10 2 A/W, detectivity of ~3.01 × 10 9 Jones in the mid-infrared range and an anisotropic ratio of ∼8 for 2.3 μm illumination to ensure polarized imaging.